Pseudotyped Viruses: A Useful Platform for Pre-Clinical Studies Conducted in a BSL-2 Laboratory Setting - Sofiia N. Rizatdinova; Alina E. Ershova; Irina V. Astrakhantseva (Biomolecules)
The study of pathogenic viruses has always posed significant biosafety challenges. In particular, the study of highly pathogenic viruses requires methods with low biological risk but relatively high sensitivity and convenience in detection. In recent years, pseudoviruses, which consist of a backbone of one virus and envelope proteins of another virus, have become one of the most widely used tools for exploring the mechanisms of viruses binding to cells, membrane fusion and viral entry, as well as for screening the libraries of antiviral substances, evaluating the potential of neutralizing monoclonal antibodies, developing neutralization tests, and therapeutic platforms. During the outbreak of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), pseudotyped virus-based assays played a pivotal role in advancing our understanding of virus–cell interactions and the role of its proteins in disease pathogenesis. Such tools facilitated the search for potential therapeutic agents and accelerated epidemiological studies on post-infection and post-vaccination humoral immunity. This review focuses on the use of pseudoviruses as a model for large-scale applications to study enveloped viruses.